2017
DOI: 10.1055/s-0043-113038
|View full text |Cite
|
Sign up to set email alerts
|

Musikalische Fähigkeiten bei Kindern mit auditiver Verarbeitungs- und Wahrnehmungsstörung

Abstract: Difficulties in solving musical tasks are observed in clinical practice in children with an auditory processing disorder (APD). There is a paucity of research on musical ability in children with an APD. To assess musical skills we had 15 children aged 6-11 years with the diagnosis of APD perform a test, and compared them to a control group of 15 children. APD children did significantly worse in pitch discrimination, reproduction of rhythm and singing. Correlations between language-based and musical skills in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Poor musical ability and/or appreciation of music is a common selfreported symptom by children with APD (American Academy of Audiology [AAA], 2010). Olakunbi et al (2010) reported poorer meter perception and Scheffner et al (2017) reported poorer rhythm reproduction in children with APD compared to neurotypical ones. Dyslexic children also show compromised non-musical auditory processing and auditory rhythm perception (Goswami et al, 2013; Colling et al, 2017) while Huss et al (2011) found these measures to be correlated.…”
Section: Introductionmentioning
confidence: 91%
“…Poor musical ability and/or appreciation of music is a common selfreported symptom by children with APD (American Academy of Audiology [AAA], 2010). Olakunbi et al (2010) reported poorer meter perception and Scheffner et al (2017) reported poorer rhythm reproduction in children with APD compared to neurotypical ones. Dyslexic children also show compromised non-musical auditory processing and auditory rhythm perception (Goswami et al, 2013; Colling et al, 2017) while Huss et al (2011) found these measures to be correlated.…”
Section: Introductionmentioning
confidence: 91%
“…[7] anschaulich und prägnant, sehr lesenswert auch für diejenigen, die sich bisher mit diesem Thema nicht oder nur wenig beschäftigt haben. Musikalische Fähigkeiten von Kindern mit auditiver Verarbeitungs-und Wahrnehmungsstörung werden in diesem Heft ebenfalls beleuchtet [8].…”
unclassified